Yamarna Geology: Foundations for Further Discovery. Issue 1 (1st December 2019) - Tunjic, Janet; Donaldson, John; Osborne, Justin; Davy's, Clayton; Berg, Rick
Summary: World class gold discoveries are being made in the Yamarna Terrane, one of the least understood terranes of the Yilgarn Craton. Despite many and varied challenges, Gold Road are in the unique position of compiling and constructing the stratigraphic map for this immature exploration terrane allowing continual improvement to ongoing targeting and exploration programmes. The key to successful exploration is the development of a regional stratigraphic and structural geological model through acquisition of new data, application of modern science, and integration of fundamental geological observation. Lithogeochemical classifications, geochronology, and development of mineralisation models are the three areas of focus Gold Road considers paramount to combine with the fundamental structure of the Yamarna Terrane. New geochronological data has implications for the understanding of the geodynamic evolution of the Yilgarn Craton, identifying some of the oldest rocks so far found in Eastern Goldfields Superterrane. A case study is presented of the development in the understanding of the tectonostratigraphic evolution of the Yamarna Terrane to target for gold efficiently and effectively.